Thyroid hormone profile and PELOD score in children with sepsis - Agung G. Tanurahardja; Antonius H. Pudjiadi; Pramita G. Dwipoerwantoro; Aman Pulungan (Indonesian Pediatric Society, 2014)
Background Thyroid hormonal dysfunction, also known aseuthyroid sick syndrome or nonthyroidal illness, can be seenin sepsis. There have been few studies on thyroid hormonedysfunction in septic children, as well as on a relationshipbetween their thyroid hormone profiles and pediatric logisticorgan dysfunction (PELOD) scores. Procakitonin (PCT) is oneof the sepsis biomarker.Objective To evaluate the thyroid hormone profile in childrenwith sepsis as well as to assess for a correlation between the thyroidlevels and PELOD scores, PCT levels, and patient outcomes.Methods This cross-sectional study included children aged 1- 18years admitted to the pediatric intensive care unit (PICU) with aprimary diagnosis of sepsis. PELOD scores and thyroid hormonallevels were assessed once during the first 24 hours after PICUadmission.Results Thirty subjects were included in the study. The medianvalues ofT3, free T4, and TSH were 45 (range 17 -133) ng/dL,0.81 (range 0.3-1.57) ng/dL, and 1.36 (range 0.05-7.78) Î¼IU/L,respectively. The T3, free T4, and TSH levels were decreased in97%, 50% and 40% of the subjects. There were no significantdifferences between low and normal to high TSH with regards tothe PELOD score (P=0.218), PCT level (P=0.694), or patientoutcomes (P=0.55). The risk of death increased by 15 timesamong the subjects with PELOD score 20 compared to thosewith PELOD score <20 (OR 15; 95%CI: 1.535 to 146.545;P=0.012).Conclusion Thyroid hormones are decreased in septic childrenwith the majority having low T3. A high PELOD score is stronglycorrelated with mortality and can be used as a prognostic parameterfor septic children in the PICU, but there is no correlation withdecreased TSH.